Problems and prospects for the survival of liberal democracy in the Commonwealth Caribbean. - Ryan, Selwyn (1992)
Identifies factors which have made Caribbean democracy appear to be unique in the ex-colonial world. Reports on contemporary events which challenge this democracy.